2013
DOI: 10.1182/asheducation-2013.1.423
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of fungal disease in the setting of neutropenia

Abstract: Invasive fungal infections are important causes of morbidity and attributable mortality in neutropenic patients with hematological malignancies, myelodysplasia, and aplastic anemia. Successful risk-based strategies can be implemented for prophylaxis, empirical therapy, and preemptive therapy for the prevention and early treatment of invasive fungal infections in neutropenic hosts. The use of echinocandins for invasive candidiasis and voriconazole for invasive aspergillosis has significantly improved outcome. R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
47
1
3

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 59 publications
(54 citation statements)
references
References 14 publications
3
47
1
3
Order By: Relevance
“…Administration of either amphotericin B or CAS is recommended for treatment of azole-resistant Candida species-related bacteremia 29. In the current study, history of antifungal use was found to be associated with azole-resistant Candida species in patients with hematological malignancies (Table 2), indicating that antifungal drug use leads to development of relevant antifungal drug-resistant strains in the environment and patients 1,30. To address this problem, periodic changes in the use of antifungal drugs, such as changing VOR to amphotericin B for invasive Aspergillus and CAS to amphotericin B for empirical antifungal treatment, could be evaluated, but performance of prospective, randomized-controlled studies is needed to identify a solution to this challenge.…”
Section: Discussionmentioning
confidence: 53%
“…Administration of either amphotericin B or CAS is recommended for treatment of azole-resistant Candida species-related bacteremia 29. In the current study, history of antifungal use was found to be associated with azole-resistant Candida species in patients with hematological malignancies (Table 2), indicating that antifungal drug use leads to development of relevant antifungal drug-resistant strains in the environment and patients 1,30. To address this problem, periodic changes in the use of antifungal drugs, such as changing VOR to amphotericin B for invasive Aspergillus and CAS to amphotericin B for empirical antifungal treatment, could be evaluated, but performance of prospective, randomized-controlled studies is needed to identify a solution to this challenge.…”
Section: Discussionmentioning
confidence: 53%
“…Recently, Nucci et al, retrospectively analyzed 233 cases of invasive fusariosis and found that neutropenia at the end of treatment was associated with poor prognosis by multivariate analysis [6]. Other authors also found that the length of neutropenia is significantly associated with a poor outcome of several fungal infections [7]. Although almost all the patients described in this review were neutropenic at the time of diagnosis of fungal infection, the length of neutropenia prior to infection as well its persistence or recovery over time were often not reported, making this point prevalence detection difficult to interpret.…”
Section: Discussionmentioning
confidence: 96%
“…This is supported by reports demonstrating that candidemia is an important complication that occurs with a high frequency in neutropenic patients [31] and that prolonged neutropenia results in susceptibility to infection by Candida spp. and Aspergillus spp.…”
Section: Disease State and Treatments Compromising Immune Competencementioning
confidence: 55%